THE USE OF TECHNOLOGY IN ENGLISH AS A FOREIGN LANGUAGE LEARNING OUTSIDE THE CLASSROOM: AN INSIGHT INTO LEARNER AUTONOMY - Warni, Silih; Aziz, Tian Abdul; Febriawan, Dimas (LLT Journal: A Journal on Language and Language Teaching, 2018)
This research was conducted to examine Indonesian students experiences in using technology in learning English outside the classroom with regards to learner autonomy as an important capacity for studentsâ learning success. The subjects of the study were students of a private Senior High School in South Tangerang. As for the methodology, this research applied quantitative and qualitative design. Quantitative elements include questionnaires as the data collecting method, while qualitative elements used semi structured interviews. In this interview, five students were chosen purposively based on studentsâ responses on the questionnaires. The findings of this study indicate that the use of technology to learn English outside the classroom has encouraged the development of learner autonomy which includes aspects of learning motivation, metacognitive awareness, self-confidence and social skills. This research is expected to help English teachers improve their students English proficiency with the concern on the development of learner autonomy by using various information and communication technology.Â DOI:Â doi.org/10.24071/llt.2018.210203